Gambaran Faktor Predisposing, Enabling dan Reinforcing KB Vasektomi - Shelly Rosalina Febrianti (Universitas Airlangga, 2019)
Background: Family Planning Program is a program that can be adopted by men and women but for male participation is still low that is 0.3%. In Surabaya, the target of vasectomy from 31 sub-districts is only 8 districts (26%) who have reached the target of active participants of KB Vasectomy. Kenjeran sub-district is one of the sub-districts that has reached the target of vasectomy and has family vasectomy group which has active participants. Purpose: The aims of this study was to identify the factors oh male participation in vasectomy contraception in the Kenjeran District of Surabaya. Methods: The design of this research is qualitative research with phenomenology approach. The research informants were 9 people, 6 were key informants ie men who followed KB vasectomy and 3 additional informants, the wife of the key informant. Results: The results showed the number of informants as many as 9 people with age range elderly. The predisposing factor showed good knowledge, attitude and belief about vasectomy method. The reinforcing factors showed most informants have the support of the wives and the male family planning group who has a role as a motivator and disseminator. The affordability cost and good service are enabling factors, men, to participate in the vasectomy method. Conclusion: The conclusion of this research is informant has the desire to participate in KB vasectomy, proved by the finding of factors that support man to do KB vasectomy.